STUDIES ON EPIDEMIOLOGICAL ASPECTS OF CANINE MAMMARY GLAND TUMOURS IN GUJARAT - Dhami , M A; Tank , P H (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Epidemiological factors like age, breed, sex, parity, breeding soundness and site and nature of involvement of mammary gland were studied in relation to occurrence of mammary tumours in 29 bitches over one year at College Hospital. Out of 29 canine mammary tumour cases, 13 (44.83 %) were found in dogs aged 4 to 8 years, 12 (41.38 %) in dogs aged 8 to 12 years and 4 (13.79 %) in dogs aged more than 12 years, but no case was seen in dogs less than 4 years old. Breed wise higher occurrence was found in German Shepherd (36.50 %) and Pomeranian (31.75 %) as compared to the other breeds and that too mainly in females (96.56 %). There was an increasing frequency of canine mammary tumours from cranial thoracic to inguinal pairs with the highest incidence in caudal abdominal (31.03 %) and the least in cranial thoracic pair (3.45 %). The involvement of inguinal, cranial abdominal and caudal thoracic glands was 27.59, 20.69 and 17.24 per cent, respectively. Most of the patients had multiple involvements of glands. Out of the 29 bitches operated for mammary tumours, 22 (75.86 %) were intact and rests 7 (24.14 %) were neutered. All the neutered bitches were spayed after the age of 4 years.
Keywords: Canine; Mammary tumour; Epidemiology; Site; Age; Sex and Breed effect